Strategies to Overcome Intermediate Accumulation During in situ Nitrate Remediation in Groundwater by Hydrogenotrophic Denitrification - Duffner, Clara; Wunderlich, Anja; Schloter, Michael; Schulz, Stefanie; Einsiedl, Florian (Frontiers in Microbiology, 2021)
Bioremediation of polluted groundwater is one of the most difficult actions in environmental science. Nonetheless, the clean-up of nitrate polluted groundwater may become increasingly important as nitrate concentrations frequently exceed the EU drinking water limit of 50 mg L–1, largely due to intensification of agriculture and food production. Denitrifiers are natural catalysts that can reduce increasing nitrogen loading of aquatic ecosystems. Porous aquifers with high nitrate loading are largely electron donor limited and additionally, high dissolved oxygen concentrations are known to reduce the efficiency of denitrification. Therefore, denitrification lag times (time prior to commencement of microbial nitrate reduction) up to decades were determined for such groundwater systems. The stimulation of autotrophic denitrifiers by the injection of hydrogen into nitrate polluted regional groundwater systems may represent a promising remediation strategy for such environments. However, besides high costs other drawbacks, such as the transient or lasting accumulation of the cytotoxic intermediate nitrite or the formation of the potent greenhouse gas nitrous oxide, have been described. In this article, we detect causes of incomplete denitrification, which include environmental factors and physiological characteristics of the underlying bacteria and provide possible mitigation approaches.